Bt Cotton in India - Pal, Rishi; Prasad, C. S. (Indian Farming, 2015)
Bt cotton provides in built protection to cotton against lepidopteron pests (Helicoverpa), therefore production of cotton has been increased. Due to introduction of Bt cotton socio-economic status of farmers has improved. The control provided by Bt cottons approaches immunity. No survivors have been found in field studies. Bt cotton has revolutionized our ability to implement IPM in cotton and reduced our insecticide inputs by over 60%.